Case Report: Clostridium neonatale Bacteremia in a Preterm Neonate With Necrotizing Enterocolitis - Cassir, Nadim; Grandvuillemin, Isabelle; Boxberger, Manon; Jardot, Priscilla; Boubred, Farid; La Scola, Bernard (Frontiers in Pediatrics, 2021)
Necrotizing enterocolitis is a life-threatening acquired gastrointestinal disorder among preterm neonates and is associated with a high mortality rate and long-term neurodevelopmental morbidity. No etiologic agent has been definitively established; nonetheless, the most implicated bacteria include members of the Clostridium genus. We reported here on a case of Clostridium neonatale bacteremia in a preterm neonate with necrotizing enterocolitis, providing more information regarding the potential role of this bacterium in pathogenesis of necrotizing enterocolitis. We emphasized the sporulating form of C. neonatale that confers resistance to disinfectants usually applied for the hospital environmental cleaning. Further works are needed to establish the causal relationship between the occurrence of NEC and the isolation of C. neonatale, with promising perspectives in terms of diagnostic and therapeutic management.